Family crisis or the crisis of writing about family? Based on the literature for teenagers at the turn of the century - Gromadzka, Beata (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The literary portraits of families reveal a structural, cultural and emotional stereotype which does not provide positive examples and leaves no doubt about durability of ties binding the family members. Also writings reveal the crisis of writing about family in YA literature, because the presented works lack ways to overcome cultural stereotypes and they portray the crisis instead pointing directions to which the modern family transforms to.
Keywords: Young Adult literature; teenagers; maturation; crisis in family